Association of serum level of 25-hydroxy vitamin D with Oral Lichen Planus. A case-control study. - Mostafa Sadeghi; Mahdieh Zarabadipour; Faezeh Azmodeh; Monirsadat Mirzadeh; Ali Sarbazi Golezari (Universidad de Concepción., 2020)
Introduction: Vitamin D deficiency is a global health problem that can be a risk factor for a broad range of diseases such as some autoimmune diseases. Due to the autoimmune base of lichen planus, it seems that a reduction of the serum level of vitamin D is related to lichen planus. In this study, we investigate the relation between serum level of vitamin D and oral lichen planus patients (OLP). Material and Methods: In this case-control study, 35 patients with OLP (including 15 men and 20 women) and 70 healthy volunteers (including 35 men and 35 women), aged between 30-60 years old, referred to Qazvin University of Medical Sciences were investigated. None of these volunteers had systemic diseases. Vitamin D levels were measured with ELFA (Enzyme Linked Fluorescent Assay) and the data was analyzed using the chi-squared test and t-test. Results: The mean serum level of vitamin D in the control group was 23.7±9ng/ml and in the case group was 18.12±8/7ng/ml. The results show that the serum level of vitamin D in patients with OLP is significantly less than in the control group (p<0.05). Conclusion: According to the results, the serum level of vitamin D in patients with OLP was significantly lower than that of healthy people.